Species of flabellifera (Crustacea; Isopoda) and their distribution in Icelandic waters - Anika Karen Guðlaugsdóttir 1986- (2010)
The Flabellifera (Crustacea; Isopoda) holds over 3000 described species and is the second largest isopod suborder, containing 18 families. Flabelliferans occur both in marine environment as well as in fresh water habitats, at all depths and latitudes of the world ocean. The Iceland-Faeroe Ridge is a part of the Greenland-Scotland Ridge and separates the Nordic Seas and the North Atlantic. The Greenland-Iceland-Faeroe (GIF) Ridge is relatively shallow and separates depths of more than 2000 meters on both sides and is a natural boundary between relatively warm Northeast Atlantic water and cold subarctic water masses. Iceland is located centrally on the GIF Ridge and the regions around Iceland hold a diversity of water masses, ranging in both temperature and saline concentration. The distribution of isopods (Crustacea, order Isopoda; suborder Flabellifera Sars 1882; families Aegidae Leach, 1815 and Cirolanidae Dana, 1852) were examined in Icelandic waters, based on analysis of 427 specimens collected between 1991-2004 on the GIF Ridge at 95 stations. The distributional pattern of the Flabelliferans in Icelandic waters was investigated and species assigned to water masses. Both families were species poor in the area, in total occurring with only 7 species in 4 genera. Species were found at temperatures ranging from 2.70-7.84°C and at depths from 140-2369 meters. Most species were restricted to warmer water.